Analysis of the retrofitting of a universal vacuum cryogenic spectrophotometer - Akylbayeva, A.; Sokolov, D.; Aldiyarov, A.; Golikov, O.; Karamysova, L.; Yerezhep, D. (Recent Contributions to Physics, 2023)
The paper considers the modernization of the methodology for studying astrophysical ice and cold interstellar dust. An experimental method of physical modeling using a vacuum cryogenic installation is presented. The nodes of the universal vacuum cryogenic spectrophotometer where it is necessary to modernize, retrofit for the subsequent improvement of measuring capabilities in scientific research are considered in detail. The IR spectra of polystyrene were obtained on the IRS-29 and FSM 2203 spectrometers, the results of the obtained characteristic absorption bands were compared with the values of the reference spectrum of polystyrene, and the expanded uncertainty was calculated. To assess the accuracy of the measurement results, we calculated the expanded uncertainty according to the IR spectrometer calibration procedure. The wavenumber scale calibration uncertainty was determined by direct measurements as the difference between the wavenumber value corresponding to the maximum ordinate of the absorption line of a standard polystyrene film sample. In this work, an analysis of the completed retrofitting of a universal vacuum cryogenic spectrophotometer was carried out. N2O spectra were taken, obtained at a temperature of 16 K in the wave number range of IR spectrometers from 370 to 4200 1/cm with the designation of the corresponding absorption bands. The studies carried out in this work are aimed at improving the accuracy of measurements, which guarantees and improves the quality of scientific research.
Keywords: astrophysical ice; vacuum cryogenic equipment; polystyrene